Flambagem lateral com distorção de vigas mistas de aço e concreto em situação de incêndio: análises experimental e numérica e proposta de procedimento de cálculo - João Victor Fragoso Dias (2021)
Steel and concrete continuous and semicontinuous composite beams present hogging bendingmoments near the inner supports that compress the bottom flange and tension the concrete slab. Therefore, the slab cracks and instability phenomena become possible, leading to a diferente behavior of these beams when compared to simply supported ones. Despite these problems, the consideration of continuity can still lead to an economic design, besides making the structure more robust and resistant to the effects of fire. The non-uniform heating of the cross-section and the degradation of mechanical properties may ease the occurrence of the phenomenon known as lateral-distortional buckling (LDB), which has not been, so far, described in literature at high temperatures. In this work, four experimental structural fire tests on full-scale composite beams under hogging moment are presented. The four beams presented the lateral-distortional buckling mode, accompanied by local buckling when subjected to heating. A numerical study, validated with results of these tests and from the literature was developed, producing simplified and complete models for the assessment of LDB. Then, a simplified calculation procedure for the determination of the resistant bending moment to lateral-distortional buckling in fire situation, developed in a very similar manner to what is presented in current design standards, was presented. This procedure was applied to the numerical models and the results indicate that the proposed procedure is suitable for predicting the capacity of composite beams under hogging moment and that the procedure for considering local buckling that is currently adopted by Brazilian and European design standards should be reviewed.